2020
DOI: 10.26508/lsa.201900592
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell α-defensin misfolding correlates with dysbiosis and ileitis in Crohn’s disease model mice

Abstract: Crohn’s disease (CD) is an intractable inflammatory bowel disease, and dysbiosis, disruption of the intestinal microbiota, is associated with CD pathophysiology. ER stress, disruption of ER homeostasis in Paneth cells of the small intestine, and α-defensin misfolding have been reported in CD patients. Because α-defensins regulate the composition of the intestinal microbiota, their misfolding may cause dysbiosis. However, whether ER stress, α-defensin misfolding, and dysbiosis contribute to the pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 86 publications
0
30
1
Order By: Relevance
“…In Crohn’s disease, an intractable inflammatory bowel disease, it is known that lesion formation is predominant in the terminal ileum. The amount and the quality of α-defensins in Crohn’s disease have been shedding important insights into the pathogenesis and pathophysiology of the disease ( 42 , 45 , 46 ). Bacterial overgrowth is known to occur not only in the colon but in affected lesions in the terminal ileum in patients with severe ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In Crohn’s disease, an intractable inflammatory bowel disease, it is known that lesion formation is predominant in the terminal ileum. The amount and the quality of α-defensins in Crohn’s disease have been shedding important insights into the pathogenesis and pathophysiology of the disease ( 42 , 45 , 46 ). Bacterial overgrowth is known to occur not only in the colon but in affected lesions in the terminal ileum in patients with severe ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Final DNA concentrations were determined at 260 nm using a NanoDrop 2000 spectrometer (Thermo Fischer Scientific). 16S ribosomal RNA genes were amplified by PCR from each fecal DNA sample using universal primer set of Bakt 341F (5′-cctacgggnggcwgcag) and Bakt 805R (5′-gactachvgggtatctaatcc) which covers the V3-V4 variable region 16 , 52 , 53 . PCR amplification was performed in 25-μl-volume reaction mixtures containing 12.5 ng of template DNA, 200 nM of each primer, and 1 × KAPA HiFi Hot Start Ready Mix (Kapa Biosystems) under the following conditions: 95 °C for 3 min, 25 cycles of 95 °C for 30 s, 55 °C for 30 s, and 72 °C for 30 s, followed by 72 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the absence of active α-defensin alters the composition of small intestinal microbiota in mice 14 , and oral administration of α-defensin rescues severe dysbiosis of graft-versus-host disease (GVHD) model mice 15 , indicating that α-defensin plays an important role in maintaining homeostasis of the intestinal microbiota. In addition, it has been known that α-defensin abnormalities cause dysbiosis and disruption of the intestinal metabolism in Crohn’s disease model mice 16 , 17 . Dysbiosis caused by Paneth cell damage with decreased α-defensin has been shown to relate to various diseases 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that the expression level of HD5 is decreased in patients with Crohn's disease and obesity which are known to relate to dysbiosis [74,75]. Furthermore, we have revealed that both quantitative and qualitative impairments of α-defensin secretion are associated with pathological progressions of graft versus host disease and Crohn's disease model mice via dysbiosis [40][41][42]. Taken together, it is suggested that deficiencies of α-defensin secretion relate to the increased risk of several diseases via inducing dysbiosis.…”
Section: Discussionmentioning
confidence: 52%
“…Paneth cells have intracellular secretory granules rich in antimicrobial peptide α-defensins termed cryptdins (Crps) in mice [29,30] and human defensin (HD) 5 and 6 in humans [31,32], and contribute to innate enteric immunity by secreting α-defensins into the intestinal lumen in response to bacterial stimuli [33,34], cholinergic agents [35], and certain food factors [36]. Furthermore, Paneth cell α-defensins have been known to contribute to the regulation of the intestinal microbiota in their quantity and quality-dependent manners [37][38][39][40][41][42]. It has also been reported that the supply of Wnt signals to the stem cells by Paneth cells is diminished by aging [43,44], suggesting that Paneth cell function declines with aging.…”
Section: Introductionmentioning
confidence: 99%